Acquired immune responses to three malaria vaccine candidates and their relationship to invasion inhibition in two populations naturally exposed to malaria. (December 2016) - Addai-Mensah, Otchere; Seidel, Melanie; Amidu, Nafiu; Maskus, Dominika; Kapelski, Stephanie; Breuer, Gudrun; Franken, Carmen; Owusu-Dabo, Ellis; Frempong, Margaret; Rakotozandrindrainy, Raphaël; Schinkel, Helga; Reimann, Andreas; et al.
Abstract Background Malaria still represents a major cause of morbidity and mortality predominantly in several developing countries, and remains a priority in many public health programmes. Despite the enormous gains made in control and prevention the development of an effective vaccine represents a persisting challenge. Although several parasite antigens including pre-erythrocytic antigens and blood stage antigens have been thoroughly investigated, the identification of solid immune correlates of protection against infection byPlasmodium falciparum or clinical malaria remains a major hurdle. In this study, an immuno-epidemiological survey was carried out between two populations naturally exposed toP. falciparum malaria to determine the immune correlates of protection. Methods Plasma samples of immune adults from two countries (Ghana and Madagascar) were tested for their reactivity against the merozoite surface proteins MSP1-19, MSP3 and AMA1 by ELISA. The antigens had been selected on the basis of cumulative evidence of their role in anti-malarial immunity. Additionally, reactivity against crudeP. falciparum lysate was investigated. Purified IgG from these samples were furthermore tested in an invasion inhibition assay for their antiparasitic activity. Results Significant intra- and inter- population variation of the reactivity of the samples to the tested antigens were found, as well as a significant positive correlation between MSP1-19 reactivity and invasion inhibition (p < 0.05). Interestingly, male donors showed a significantly higher antibody response to all tested antigens than their female counterparts. In vitro invasion inhibition assays comparing the purified antibodies from the donors from Ghana and Madagascar did not show any statistically significant difference. Although in vitro invasion inhibition increased with breadth of antibody response, the increase was not statistically significant. Conclusions The findings support the fact that the development of semi-immunity to malaria is probably contingent on the development of antibodies to not only one, but a range of antigens and that invasion inhibition in immune adults may be a function of antibodies to various antigens. This supports strategies of vaccination including multicomponent vaccines as well as passive vaccination strategies with antibody cocktails.